Rescue of human RET gene expression by sodium butyrate: a novel powerful tool for molecular studies in Hirschsprung disease. Issue 8 (15th July 2003) - Griseri, P; Patrone, G; Puppo, F; Romeo, G; Ravazzolo, R; Ceccherini, I
Abstract : Background: The RET gene encodes a tyrosine kinase receptor involved in different human neurocristopathies, such as specific neuroendocrine tumours and Hirschsprung disease (HSCR). Gene expression is developmentally regulated and the RET transcript is undetectable in most adult cells, including lymphocytes. The impossibility of performing functional studies on RET mRNA has to date limited the detection and characterisation of an indefinite proportion of gene anomalies that cannot be identified by conventional DNA genomic screening in HSCR cases. Aims: Development of a protocol suitable to activate RET expression in RET negative cell lines and therefore to investigate directly RET mRNA, extending the conventional gene mutation analysis to detection of splicing anomalies and impaired expression of the RET gene. Methods: The effect of sodium butyrate (NaB), a histone deacetylase inhibitor, on rescuing RET expression was tested by one round of reverse transcription- polymerase chain reaction from total RNA of treated lymphoblasts from both HSCR patients and control individuals. Results: Analysis of RET expression was possible by NaB treatment of RET negative cells, such as lymphoblasts. This treatment allowed us to detect impaired RET expression as well as a splicing defect in two HSCR patients previously believed to be devoid of any gene abnormality. Conclusions: The full application of the proposed protocol in most of the unexplained HSCR cases will allow us to establish the precise role of RET not only in causing but also in predisposing to HSCR pathogenesis.